Environmental accounting and reporting : theory and practice - Baldarelli, Maria Gabriella; Del Baldo, Mara; Nesheva-Kiosseva, Ninel (Springer, 2017)
This book discusses the foundations of social and environmental accounting and highlights local differences in countries like Italy and Bulgaria. It also describes the institutional environment, which affects the development and application of environmental accounting and reporting, as a basis for evaluating current achievements and the future steps that need to be taken to develop and spread environmental accounting. The book is unique in presenting exemplary cases from different emerging and developed countries. It is a valuable resource for theorists in the field, practitioners in companies, as well as investors and other stakeholders. Moreover, it provides students with the necessary theoretical constructs, empirical studies as well as practical and managerial tools to allow for a quick orientation in the methodology, techniques and selected practices used in environmental accounting and reporting.
Keywords: Environmental auditing.; Environmental reporting.; elektronické knihy; electronic books